Transition Metal-Mediated Preparation of Nitrogen-Doped Porous Carbon for Advanced Zinc-Ion Hybrid Capacitors - Mingcheng Li; Zheng Liu; Dan Wu; Huihao Wu; Kuikui Xiao (Nanomaterials)
Carbon is predominantly used in zinc-ion hybrid capacitors (ZIHCs) as an electrode material. Nitrogen doping and strategic design can enhance its electrochemical properties. Melamine formaldehyde resin, serving as a hard carbon precursor, synthesizes nitrogen-doped porous carbon after annealing. Incorporating transition metal catalysts like Ni, Co, and Fe alters the morphology, pore structure, graphitization degree, and nitrogen doping types/proportions. Electrochemical tests reveal a superior capacitance of 159.5 F g−1 at a scan rate of 1 mV s−1 and rate performance in Fe-catalyzed N-doped porous carbon (Fe-NDPC). Advanced analysis shows Fe-NDPC’s high graphitic nitrogen content and graphitization degree, boosting its electric double-layer capacitance (EDLC) and pseudocapacitance. Its abundant micro- and mesopores increase the surface area fourfold compared to non-catalyzed samples, favoring EDLC and fast electrolyte transport. This study guides catalyst application in carbon materials for supercapacitors, illuminating how catalysts influence nitrogen-doped porous carbon structure and performance.